ANALISIS MANAJEMEN LABA PADA PERBANKAN SYARIAH - Astri Faradila; Ari Dewi Cahyati (JRAK: Journal of Accounting Research and Computerized Accounting, 2013)
This study determine and analyze the existence of earnings management in financial report of Islamic banks in order to prove the performance of Islamic banks in conducting their business activities. Using descriptive qualitative method with documentation data collecting, this study will disclose the fact of Shari’ Bank operation and earnings management by the manager . Based on the evidence gathered in financial reports, the minimum value of Discretionary Accrual (DACC ) for 2011 is - 5.02E - 12 , and 1.142E - 11 is the maximum value . And for 2012 , the minimum value of Discretionary Accrual ( DACC ) is - 1.49E - 11 , 5.528E - 12 is the maximum value. The result of this study is DACC of Shari’ Bank has positive and negative value. This means, there is earning management in financial statement of Shari’ Bank for 2 years, 2011 and 2012. To reduce earning management in Shari’ Bank, Dewan Pengawas Syariah (DPS) need the competent people to maximize its function.